Morbidity and school absence caused by asthma and wheezing illness. Issue 10 (October 1983) - Anderson, H R; Bailey, P A; Cooper, J S; Palmer, J C; West, S
Abstract : A survey in the London Borough of Croydon was conducted among an entire school cohort, aged about 9 years, to describe the current morbidity from wheezing illness, its relation to social and family factors, and its effects on social and educational development. A postal screening questionnaire was sent to 5100 parents, and 11.1% of the children were reported to have had wheezing illness over the previous 12 months. A sample of 284 parents were subsequently interviewed at home about their child's illness. School absence over the past year caused by wheezing illness was reported by 58%; and in 12% of children this amounted to more than 30 school days. School absence was strongly associated with all other indicators of morbidity– short and long term. The proportion described as having "asthma' rose from 22% in those with no absence, to 50% in those with more than 30 days absence. Compared with 92 randomly selected controls with no history of wheezing, wheezy children had more atopic conditions, recurrent headaches, and abdominal pains. School absence was associated with parental separation, non-manual occupation of the mother, more than three children in the household, poor maternal mental health, lack of access to a car, and renting of accommodation. The child's illness had substantial effects on the activities of the mother and the rest of the family, but not on the child's social and recreational activities. Children with over 6 weeks' school absence scored appreciably worse on a teacher's assessment of their social, psychological, and educational adjustment.